A new x-shaped copolymer role in poly(L-lactide) shape memory. (October 2019) - Ren, Yajun; Cui, Xinxiang; Wang, Lei; Wang, Yanhe; Han, Libin; Zhou, Qifeng; Song, Xiaofeng
Graphical abstract: A x -shaped polymer is designed by using tetramethyltetravinylcyclotetrasiloxane as centronucleus and polytetrahydrofuran- co -poly( ε -caprolactone) as branch to achieve PLLA shape memory. Highlights: A x -shaped polymer is devised by using tetramethyltetravinylcyclo-tetrasiloxane as centronucleus and polytetrahydrofuran- co -poly( ε -caprolactone) as branches. The syntesized product provides PLLA with shape memory characteristics. The shape memory has good repeatability. Abstract: Thermo-responsive shape memory polymers which are a class of important smart materials can recover permanent shape from temporary shape by simple thermal stimulus, but most of the polymers lack of biodegradability and biocompatibility. Poly(L-lactide) (PLLA) is a green degradable thermoplastic, however, only limited studies involve controlling its shape change. In the work, a new x -shaped copolymer with defined architecture has been devised by using tetramethyltetravinylcyclotetrasiloxane (D4 vi ) as centronucleus and polytetrahydrofuran- co -poly( ε -caprolactone) (PTMG- co -PCL) as branch to achieve PLLA shape memory. When the weight ratio of DAPP and PLLA is 50/50, the composite exhibits good thermo-responsive shape memory capacity because a balance between Tm of the x -shaped polymer rand Tg of PLLA is kept. The shape fixation ratio is 84% at 15 °C, and the recovery ratio 94% at 55 °C. And the shape memory capability does not change evidently after the reversible spiral transition is repeated for 30 times. At the same time, the composite shows great flexibility. So the obtained composite is promising for medical and bionic devices, self-healing systems, self-assembly structures.